Physiological Effects on Coexisting Microalgae of the Allelochemicals Produced by the Bloom-Forming Cyanobacteria Synechococcus sp. and Nodularia Spumigena - Śliwińska-Wilczewska, Sylwia (Toxins (Basel), 2019)
Only a few studies have documented the physiological effects of allelopathy from cyanobacteria against coexisting microalgae. We investigated the allelopathic ability of the bloom-forming cyanobacteria Synechococcus sp. and Nodularia spumigena filtrates on several aspects related to the physiology of the target species: population growth, cell morphology, and several indexes of photosynthesis rate and respiration. The target species were the following: two species of green algae (Oocystis submarina, Chlorella vulgaris) and two species of diatoms (Bacillaria paxillifer, Skeletonema marinoi). These four species coexist in the natural environment with the employed strains of Synechococcus sp. and N. spumigena employed. The tests were performed with single and repeated addition of cyanobacterial cell-free filtrate. We also tested the importance of the growth phase in the strength of the allelopathic effect. The negative effects of both cyanobacteria were the strongest with repeated exudates addition, and generally, Synechococcus sp. and N. spumigena were allelopathic only in the exponential growth phase. O. submarina was not negatively affected by Synechococcus filtrates in any of the parameters studied, while C. vulgaris, B. paxillifer, and S. marinoi were affected in several ways. N. spumigena was characterized by a stronger allelopathic activity than Synechococcus sp., showing a negative effect on all target species. The highest decline in growth, as well as the most apparent cell physical damage, was observed for the diatom S. marinoi. Our findings suggest that cyanobacterial allelochemicals are associated with the cell physical damage, as well as a reduced performance in respiration and photosynthesis system in the studied microalgae which cause the inhibition of the population growth. Moreover, our study has shown that some biotic factors that increase the intensity of allelopathic effects may also alter the ratio between bloom-forming cyanobacteria and some phytoplankton species that occur in the same aquatic ecosystem.